(untitled) (Research, Society and Development, 2023)
Termite syrup, freely sold at fairs, has anti-flu, anti-inflammatory and expectorant properties and is considered 100% natural. Thus, the work aimed to evaluate the physical-chemical, organoleptic and microbiological parameters in termite syrups sold in two different fairs in the metropolitan region of Belém do Pará. Two samples of termite syrup sold in the Ver-o market were acquired. -Weight, and at the Aurá fair, located in the Aurá neighborhood and the physical-chemical aspects (pH, density, viscosity and determination of volume and soluble solids), microbiological aspects (laurel broth, E.Coli and Salmonella) and organoleptics (color, odor and appearance). The results of the physical-chemical, microbiological and organoleptic analyzes were in accordance with the established parameters. Therefore, routine studies are needed on freely sold syrups, such as termite syrup, regarding physical-chemical and microbiological quality controls so that they do not pose a risk to consumer safety and health.